Pemberdayaan UMKM Melalui Pelatihan Strategi dan Desain Marketing serta Optimalisasi Layanan di Majapahit Food Centre Era New Normal Pasca Pandemi COVID-19 - Isra Dewi Kuntary Ibrahim; Rini Anggriani; Erwin Suhendra; Irwan Cahyadi; Raden Bagus Faizal Irany Sidharta; Ni Kadek Ira Kusumawardani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The purpose of this training is to increase the knowledge of students during “new normal” era through training on sustainable marketing strategies. They are expected to survive and to produce product or service competitiveness that is able to compete in competitive competition. In addition, training is carried out to provide added value and increases various marketing mixed strategies which include 4P’s (Product, Place, Price and Promotion). The method of implementing this service program is carried out by early identification who are related to the problems and obstacles faced by students. Therefore, both parties carry out the program by three steps which are preparation of materials, training or socialization, and recommendations.